Arbitration in disputes of international administrative contracts An analytical study - األشخاذ اىسنخٔر غتساىٍيم ُٗٔس ٌدٍس; اىٍسرس اىسنخٔر ٌدٕ اىسَٗ خصَ ٗٔشف (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Arbitration in local and international administrative contracts seem to impose itself on the various legal systems of States, especially in front of the decline the role of the national judiciary and the suspicion on it, the State permissible person becomes a side and mediator when disputes related to the administration goes to the national judiciary as the result of setbacks of this judiciary and the suffering from complexity of procedures and dysfunctional governance. We are in front of the open approach to the new Iraq and the Kurdistan region towards creating opportunities to foreign investments and encouraging them to come to our country to support national economy and development, we wonder what will happen to the internal and international administrative contract? Will it remain as a means of administrative work as opposed to the maintain of the foreign contractor to include in the administrative contract arbitration clause? All of these make prediction of the incapability of the theory of administrative contract is a real issue, especially in light of the noticeable increase in the level of willingness of the contracting parties to use arbitration to resolve the conflicts of contract and prefer to apply the laws that do not distinguish between private contracts and administrative contracts. Consequently, this situation leads to depriving the national judiciary administrative or ordinary to decide on a fundamental part of its jurisdiction in disputes related to public administration, including administrative contracts.